2008
DOI: 10.1158/0008-5472.can-07-2081
|View full text |Cite
|
Sign up to set email alerts
|

The Kringle 1 Domain of Hepatocyte Growth Factor Has Antiangiogenic and Antitumor Cell Effects on Hepatocellular Carcinoma

Abstract: The kringle 1 domain of human hepatocyte growth factor (HGFK1) was previously shown to inhibit bovine aortic endothelial cell proliferation, suggesting that it might be an antiangiogenic molecule. Here, we evaluated the in vivo efficacy of a recombinant adenoassociated virus carrying HGFK1 (rAAV-HGFK1) for the treatment of hepatocellular carcinoma (HCC) in a rat orthotopic HCC model and explored its molecular mechanisms in vitro in both endothelial and tumor cells. We first showed that rAAV-HGFK1 treatment sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…In fact, the uncleavable mutant form of HGF/SF (arginine 494 mutated to glutamic acid) can even function as a competitive inhibitor to wild-type HGF/SF (Gherardi et al 2006). In addition, the a chain of HGF/SF is susceptible to proteolysis by coagulation factor Xa (and possibly by other proteases), generating N-domain and kringle fragments that possess their own intrinsic activity in some circumstances (Rubin et al 2001;Pediaditakis et al 2002;Shen et al 2008). HGF/SF also has two shorter splice variants, the amino-terminal domain plus either one or two kringle domains (NK1 and NK2) (Stahl et al 1997), which can act as agonists or antagonists depending on the conditions and assay used (Montesano et al 1998).…”
Section: Structural Characteristics Of Met and Hgf/sfmentioning
confidence: 99%
“…In fact, the uncleavable mutant form of HGF/SF (arginine 494 mutated to glutamic acid) can even function as a competitive inhibitor to wild-type HGF/SF (Gherardi et al 2006). In addition, the a chain of HGF/SF is susceptible to proteolysis by coagulation factor Xa (and possibly by other proteases), generating N-domain and kringle fragments that possess their own intrinsic activity in some circumstances (Rubin et al 2001;Pediaditakis et al 2002;Shen et al 2008). HGF/SF also has two shorter splice variants, the amino-terminal domain plus either one or two kringle domains (NK1 and NK2) (Stahl et al 1997), which can act as agonists or antagonists depending on the conditions and assay used (Montesano et al 1998).…”
Section: Structural Characteristics Of Met and Hgf/sfmentioning
confidence: 99%
“…11 Recently, some researchers demonstrated that EGF-like ligands have the ability to strongly stimulate osteoclastogenesis in an EGFR-dependent manner. 12 We wondered if HGFK1 might be a key regulator during the process of breast cancer metastasis to bone and osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that HGFK1 exerts both antiangiogenic and antitumor activities in hepatocellular carcinoma through the epidermal growth factor (EGF)/epidermal growth factor receptor (EGFR) signaling pathway. 11 A recent report demonstrated that EGF-like ligands have the ability to strongly stimulate osteoclastogenesis in an EGFR-dependent manner. 12 Based on these findings, we wondered if HGFK1 might be a key regulator during the process of breast cancer metastasis to bone and osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition effects on MECs and tumor cell worked mainly through EGF/EGFR signaling, with more minor contributions from VEGF/VEGFR and bFGF/bFGFR signaling. It may thus be considered as a novel therapeutic strategy for the treatment of HCC (Nie et al, 2008;Shen et al, 2008a;Shen et al, 2008b). Certainly, substantial evidence from clinical data is needed to for HGFK1 to be a potential target for anticancer drugs.…”
Section: Hgfk1 Is Associated With a Better Prognostis And Reverses Inmentioning
confidence: 99%